2012
DOI: 10.4067/s0718-58392012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Perennial grasses traits as functional markers of grazing intensity in basaltic grasslands of Uruguay

Abstract: Natural grasslands in the basaltic region of Uruguay are threatened by an increase in stocking rates and changes in land use. To assess the effect of grazing intensification, plant functional types are proposed as simple tools to aid the monitoring and management of vegetation. In the present study we evaluated the effect of stocking rate increase at community level taking into account plant traits of 23 dominant perennial grass species. In order to identify plant functional types, we determined the grazing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…The sensitivity of stems was higher than that of leaves with the increase of grazing exclusion time, indicating that L. chinensis can exhibit rapid pant growth by promoting stem elongation. A previous study on leaf traits indicated that the strategies for stability and plant protection under grazing disturbance provides some indirect evidence for our findings ( Jaurena et al, 2013 ).…”
Section: Discussionsupporting
confidence: 68%
“…The sensitivity of stems was higher than that of leaves with the increase of grazing exclusion time, indicating that L. chinensis can exhibit rapid pant growth by promoting stem elongation. A previous study on leaf traits indicated that the strategies for stability and plant protection under grazing disturbance provides some indirect evidence for our findings ( Jaurena et al, 2013 ).…”
Section: Discussionsupporting
confidence: 68%
“…This preferential grazing promotes heterogeneity by creating a mosaic of patches under different grazing pressures in the landscape, with the selection of plants that share traits compatible with each local disturbance [7,8]. Conversely, grazing exclusion, or very low grazing intensities, may benefit species with certain traits, such as the tussock habit of many C4 grasses (e.g., [14,15]), and ligneous species such as shrubs [16]. In the absence of disturbance, such species may dominate, homogenize, and ultimately change the structure of large patches via competitive exclusion [17,18], and these effects may be detected in different spatial components of diversity [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…Major advances have occurred in the recent years in understanding the plant–animal relationships at Campos biome (Carvalho et al ; Nabinger et al ; Cruz et al ; Da Trindade et al , ; Jaurena et al ). These works showed the benefits of moderate grazing intensity on plant diversity, functional types composition, pasture productivity, and animal performance.…”
Section: Introductionmentioning
confidence: 81%